Virtual teams and management challenges - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2009)
As a result of globalization and advances in information and communication technologies, the increased use of virtual teams in business has become prominent. In the competitive environment companies are obliged to produce more rapidly, more effectively and more efficiently. It is necessary for them to put together different capabilities and services with the goal, through cooperation between suppliers and customers, service providers and scientific institutions to achieve firm’s objective with high quality. Nowadays shift from serial to simultaneous and parallel working in entity has become more commonplace. Literatures have shown that collaboration is as a meta-capability for companies. This article after define a virtual teams and its characteristics, addressing virtual environments and relationship with different challenges which organization should deal them such as management and employee challenges. Finally conclude that managers of company should invest less in tangible assets, but more in virtual team to generate knowledge, and in their employees’ creativity to stimulate incremental innovations in already existing technologies that will directly generate their future competitive advantage. Companies must educate everyone, not just virtual employees, on the virtual team culture but both employees and managers need to understand the dealing aspects with virtual team.